Choice of analysis pathway dramatically affects statistical outcomes in breaking continuous flash suppression - James Allen Kerr (Nature Portfolio, 2017)
Abstract Breaking Continuous Flash Suppression (bCFS) has been adopted as an appealing means to study human visual awareness, but the literature is beclouded by inconsistent and contradictory results. Although previous reviews have focused chiefly on design pitfalls and instances of false reasoning, we show in this study that the choice of analysis pathway can have severe effects on the statistical output when applied to bCFS data. Using a representative dataset designed to address a specific controversy in the realm of language processing under bCFS, namely whether psycholinguistic variables affect access to awareness, we present a range of analysis methods based on real instances in the published literature, and indicate how each approach affects the perceived outcome. We provide a summary of published bCFS studies indicating the use of data transformation and trimming, and highlight that more compelling analysis methods are sparsely used in this field. We discuss potential interpretations based on both classical and more complex analyses, to highlight how these differ. We conclude that an adherence to openly available data and analysis pathways could provide a great benefit to this field, so that conclusions can be tested against multiple analyses as standard practices are updated.